Mapping Polycomb Response Elements at the Drosophila melanogaster giant Locus. - Abed, J.A.; Cheng, C.L.; Crowell, C.R.; Madigan, L.L.; Onwuegbuchu, E.; Desai, S.; Benes, J.; Jones, R.S. (G3 : genes - genomes - genetics, 2013)
Polycomb-group (PcG) proteins are highly conserved epigenetic transcriptional regulators. They are capable of either maintaining the transcriptional silence of target genes through many cell cycles or enabling a dynamic regulation of gene expression in stem cells. In Drosophila melanogaster, recruitment of PcG proteins to targets requires the presence of at least one polycomb response element (PRE). Although the sequence requirements for PREs are not well-defined, the presence of Pho, a PRE-binding PcG protein, is a very good PRE indicator. In this study, we identify two PRE-containing regions at the PcG target gene, giant, one at the promoter, and another approximately 6 kb upstream. PRE-containing fragments, which coincide with localized presence of Pho in chromatin immunoprecipitations, were shown to maintain restricted expression of a lacZ reporter gene in embryos and to cause pairing-sensitive silencing of the mini-white gene in eyes. Our results also reinforce previous observations that although PRE maintenance and pairing-sensitive silencing activities are closely linked, the sequence requirements for these functions are not identical.